Chimeric antigen receptor T-cell therapy following autologous transplantation for secondary central nervous system lymphoma: A case report. Issue 44 (5th November 2021) - Yagi, Yu; Kanemasa, Yusuke; Ohigashi, An; Morita, Yuka; Tamura, Taichi; Nakamura, Shohei; Otsuka, Yuki; Kishida, Yuya; Kageyama, Akihiko; Shimizuguchi, Takuya; Toya, Takashi; Shimizu, Hiroaki; et al.
Abstract: Rationale: Chimeric antigen receptor (CAR) T-cell therapy is effective in treating relapsed and refractory B-cell non-Hodgkin lymphoma. However, because of the mortality risk associated with immune effector cell-associated neurotoxicity syndrome and pseudoprogression, patients with central nervous system (CNS) involvement are less likely to receive CAR T-cell therapy. Patients concerns: We report a case of a 61-year-old, male patient with intravascular large B-cell lymphoma who suffered a CNS relapse after standard chemotherapy. Diagnosis: A diagnosis of intravascular large B-cell lymphoma with CNS involvement was made. Interventions: We treated the patient using CAR T-cell therapy following a conditioning regimen consisting of thiotepa and busulfan and autologous stem cell transplantation. Although he experienced grade 1 cytokine release syndrome, no other serious adverse events, such as immune effector cell-associated neurotoxicity syndrome or pseudoprogression, were observed. Outcomes: The patient achieved complete remission after the CAR T-cell infusion. Lessons: CAR T-cell therapy following autologous stem cell transplantation is a viable option for relapsed/refractory lymphoma with CNS infiltration. Further clinical studies are warranted to verify its safety and efficacy.